A method for preparing a TBC solar cell

The method of forming an oxidation barrier layer by combining single-layer i-poly-Si layer with ultraviolet laser oxidation is solved, and the problems of uneven thermal stress distribution and high cost in the preparation of TBC solar cells are realized, which is an efficient and low-cost preparation process, which improves the Product performance and yield rate.

CN118782688BActive Publication Date: 2024-12-27HENGDIAN GRP DMEGC MAGNETICS CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411266731.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-27
Estimated Expiration
2044-09-11

AI Technical Summary

Technical Problem

In the existing TBC solar cell preparation method, poly-Si is required to deposit twice on the back of the silicon wafer, resulting in uneven thermal stress distribution, abnormal problems such as silicon wafer warping and debris appear, which affects product performance, and has low yield and deposition. The amount of special gas required for double-layer poly-Si increases the preparation cost.

Method used

The single-layer i-poly-Si layer is combined with ultraviolet laser oxidation to form an oxidation barrier layer. Through primary i-poly-Si deposition and primary laser groove technology, the preparation of TBC solar cells is realized, the process flow is simplified, and the performance and yield rate are improved. Reduce production costs.

Benefits of technology

This method effectively avoids the uneven distribution of thermal stress caused by multiple i-poly-Si deposition, reduces silicon wafer damage, improves Voc, and significantly reduces the special gas usage, improves product performance and yield, and provides A simple, efficient and low-cost preparation method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118782688B_ABST
    Figure CN118782688B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of solar cells, and discloses a method for preparing a TBC solar cell. The present invention adopts a single i-poly-Si layer combined with ultraviolet laser oxidation to form a mask for doping diffusion to obtain a TBC solar cell. The entire preparation process only requires one i-poly-Si deposition and one laser grooving, which can avoid the uneven distribution of thermal stress caused by multiple i-poly-Si depositions, resulting in reduced product performance and yield. At the same time, one laser grooving can reduce damage to silicon wafers and improve V oc ; In addition, the use of one-time i-poly-Si deposition can also significantly reduce the amount of special gases used and reduce production costs. In addition, in the TBC solar cell prepared by the method of the present invention, the i-poly-Si layer on the back of the silicon wafer forms n + The height of the ‑poly‑Si layer is basically consistent, which is helpful for the preparation of subsequent electrode layers and can further improve product performance and yield.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of solar cells, and in particular to a method for preparing a TBC solar cell. Background Art

[0002] The Chinese name of IBC cell is cross-finger back contact cell. There is no metal grid line on the front of this type of cell. The positive / back side and the corresponding positive and negative metal electrodes are integrated in the back of the cell in a cross-finger shape. This unique structure avoids the metal grid line electrode from blocking the light (~3%). Combined with the pyramid structure and anti-reflection layer on both the front and back sides, it maximizes the use of incident light. Compared with solar cells with other technical routes such as PERC and TOPCon, it can reduce more optical losses, has a higher short-circuit current, and can effectively improve the photoelectric conversion efficiency. IBC cells mainly improve conversion efficiency by changing the structure, and are a relatively pure single-sided cell. As a post-TOPCon+ technology, TBC solar cells combine TOPCon's excellent tunneling oxidation / doped polysilicon passivation contact structure technology, and are expected to become a new generation of mass-produced cells.

[0003] The current preparation of TBC solar cells usually requires sequential deposition of p + -poly-Si (≥ 200nm), n + -poly-Si (≥ 200 nm) and then formed by corresponding laser grooving process. For example, Chinese patent No. CN116845140A discloses a method for preparing TBC solar cells, including: structuring and alkali polishing of silicon wafers, depositing a first tunneling SiO x layer and the first polysilicon layer, boron doping to form a mask BSG layer, the first groove and cleaning, the back deposition of the second tunnel SiO x The second polysilicon layer, phosphorus doping to form a mask PSG layer, the second slotting, cleaning and double-sided texturing, back deposition of AlO x SiN is deposited on the back and front sides of the x The TBC solar cell formed by this scheme uses the characteristics of the mask that does not react with alkali solution, and then laser local ablation and wet chemical cleaning treatment to repair laser damage and wash away the doping atoms remaining on the surface during laser ablation. At the same time, the front and back grooved areas are textured to improve the front surface passivation performance, enhance the long-wavelength light response, and increase the cell open circuit voltage, thereby further improving the cell conversion efficiency.

[0004] However, in this type of process, since poly-Si needs to be deposited twice on the back of the silicon wafer, uneven thermal stress distribution is prone to occur, which may lead to abnormal problems such as silicon wafer warping and fragmentation, affecting product performance and resulting in a low yield rate. At the same time, the amount of special gas required to deposit a double layer of poly-Si is also greatly increased, increasing the preparation cost. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a method for preparing a TBC solar cell. The present invention obtains a TBC solar cell by doping and diffusion through a single i-poly-Si layer combined with ultraviolet laser oxidation to form an oxidation barrier layer. The whole process of the method only requires one i-poly-Si deposition and one laser grooving process, which can effectively improve the performance and yield of the product and significantly reduce the production cost. In addition, the use of ultraviolet laser oxidation to form an oxidation barrier layer is a simple, efficient and low-cost method, which is expected to be used on a large scale in production lines.

[0006] The specific technical solution of the present invention is: a method for preparing a TBC solar cell, which specifically comprises the following steps:

[0007] S1. Double-sided polishing of silicon wafers.

[0008] S2, deposit tunneling SiO on the back of the silicon wafer x layer, i-poly-Si layer.

[0009] S3, using ultraviolet laser to pattern and oxidize the surface of the i-poly-Si layer once, forming a first oxidation barrier layer. The patterned first oxidation barrier layer and the subsequent second oxidation barrier layer are interdigitated and complementary, and the two together just cover the entire i-poly-Si layer. The first oxidation barrier layer corresponds to the n in the subsequent process. + -ploy-Si (phosphorus-doped polysilicon) layer, the unblocked area is diffused by boron atoms during the boron diffusion process to form p + -ploy-Si (boron-doped polysilicon) layer; the second oxide barrier layer corresponds to the subsequent process p + -ploy-Si layer, the unblocked area is diffused by phosphorus atoms to form n + -ploy-Si layer.

[0010] During the ultraviolet laser oxidation process, oxygen or ozone is dissociated into oxygen ions under the action of the laser emitted by the ultraviolet laser. The oxygen ions react with the surface of the silicon wafer to form a silicon oxide layer (oxidation barrier layer) as a mask. During this process, the laser emitted by the laser heats the silicon wafer at the same time, which is conducive to promoting the rapid oxidation reaction of oxygen ions with the silicon wafer to form a silicon oxide layer as a mask. The mask preparation can be completed quickly. Compared with the method of preparing the mask by deposition process, the mask preparation time can be greatly shortened, and the mask preparation efficiency and preparation accuracy can be improved.

[0011] S4, the i-poly-Si layer containing the first oxidation barrier layer is subjected to boron diffusion. Boron atoms in the region with the first oxidation barrier layer are difficult to enter the bottom i-poly-Si layer, so that the intrinsic polysilicon characteristics can still be maintained; the i-poly-Si layer in the region without the oxidation barrier layer can be transformed into p-type silicon during the boron diffusion process. + -poly-Si layer, and at the same time generate a BSG layer (borosilicate glass layer) on the surface.

[0012] S5, removing the first oxidation barrier layer and the BSG layer. The first oxidation barrier layer and the BSG layer covering the surface of the i-poly-Si layer are removed. + -The BSG layer on the surface of the p-ploy-Si layer is for the subsequent + The surface of the -poly-Si layer is oxidized by ultraviolet laser to form a second oxidation barrier layer, and the remaining i-poly-Si layer is exposed to the outside for phosphorus diffusion, which facilitates the entry of phosphorus atoms. After removing the first oxidation barrier layer and BSG layer, the back of the silicon wafer is a cross-spaced i-poly-Si layer and p-poly-Si layer. + -ploy-Si layer.

[0013] S6, using UV laser secondary patterning p + -poly-Si layer surface, forming a second oxidation barrier layer.

[0014] S7, diffuse phosphorus into the area without the second oxidation barrier layer to generate n + -poly-Si layer and PSG layer (phosphosilicate glass layer).

[0015] S8, remove the wrapping coating on the front and side of the silicon wafer. The present invention specifically removes the wrapping coating before laser grooving because the wrapping coating is generally removed by etching with an acid mixture to remove excess P + -ploy-Si layer and n + -poly-Si layer, if the groove is opened first and then the plating layer is removed, the i-poly-Si layer or the tunneling SiO x The layer or the silicon wafer itself is corroded by the acid, thus affecting the performance of the battery after preparation.

[0016] S9, in p + -poly-Si layer and n + -Laser grooving at the junction of poly-Si layers.

[0017] S10, double-sided texturing and cleaning to remove the second oxidation barrier layer and the PSG layer.

[0018] S11, double-sided coating, to form a passivation anti-reflection layer on the front and back sides. The passivation anti-reflection layer is plated on the surface of the preliminarily prepared silicon wafer. Its purpose is to: (1) reduce surface carrier recombination and improve V oc ; (2) Reduce light reflection and increase light absorption, thereby increasing photocurrent.

[0019] S12, screen printing, sintering, and light injection to obtain a TBC solar cell.

[0020] In the above preparation method, the present invention first performs double-sided polishing on the silicon wafer, and then deposits tunneling SiO x layer and i-poly-Si layer; then based on the single layer of i-poly-Si layer, its surface is predetermined as n + -ploy-Si layer area and p + The graphic range of the i-poly-Si layer area is firstly formed on the surface of the i-poly-Si layer corresponding to the n-poly-Si layer by ultraviolet laser oxidation treatment. + The first oxide barrier layer is formed in the area of ​​the -ploy-Si layer for protection, and boron is diffused into the unprotected area to generate p + -ploy-Si layer; after removing the first oxidation barrier layer and the BSG layer, in the same way, the already formed p + A second oxide protective layer is formed on the surface of the i-poly-Si layer to protect it, and phosphorus is diffused into the unprotected i-poly-Si layer to generate n + -poly-Si layer; thus completing P on the single i-poly-Si layer + Area (p + -ploy-Si) and N + Area (n + -ploy-Si) is generated, and then the junction of the two areas is laser grooved to achieve insulation isolation, and then texturing, double-sided coating and electrode layer are performed to finally produce TBC solar cells.

[0021] As described in the background technology section of the present application, in the prior art, the entire preparation process usually requires multiple depositions of polysilicon layers (i-poly-Si layers) and multiple laser grooving. Among them, multiple depositions are prone to uneven distribution of thermal stress, which can lead to abnormal problems such as warping and fragmentation of silicon wafers, and a low yield rate; at the same time, multiple laser grooving will increase damage to silicon wafers; in addition, multiple depositions will greatly increase the amount of special gases used, increasing production costs. In the entire preparation process of the present invention, only one i-poly-Si deposition is required, which can avoid problems such as uneven distribution of thermal stress caused by multiple i-poly-Si depositions leading to reduced yield; at the same time, one laser grooving can reduce damage to the silicon wafer and improve V oc ; In addition, the use of one-time i-poly-Si deposition can also significantly reduce the use of special gases and reduce production costs. In addition, the present invention uses laser oxidation to form a mask (oxidation barrier layer) on the surface of the silicon wafer, which is a simple, efficient and low-cost method and is expected to be used on a large scale in production lines.

[0022] Preferably, in S3, the process of forming the first oxidation barrier layer comprises: once patterning and oxidizing the i-poly-Si layer with an ultraviolet laser, at a preset n + -poly-Si region forms a first oxidation barrier layer; the wavelength of the ultraviolet laser is 300-400 nm, the power is 10-500 W, and the processing time is 1-20 s; a first oxidation barrier layer with a thickness of 20-300 nm is generated.

[0023] As another preferred embodiment, in S3, the first oxidation barrier layer is formed by firstly performing ultraviolet laser oxidation treatment in a low-concentration oxygen environment and then performing ultraviolet laser oxidation treatment in a high-concentration oxygen environment, so as to finally form a dense first oxidation barrier layer. Specifically, the process includes:

[0024] First, under the conditions of 10-100 sccm O2 flow rate, 20-30% oxygen concentration in the environment, 300-400 nm UV laser wavelength, 10-500 W power, and 1-20 s treatment time, the pre-set n + -A first oxidation barrier layer with a thickness of 20 to 300 nm is generated on the surface of the poly-Si layer area.

[0025] Then, under the conditions of an O2 flow rate of 100-500 sccm, an oxygen concentration of 30-80% in the environment, an ultraviolet laser wavelength of 200-300 nm, a power of 2-50 W, and a processing time of 1-20 s, a denser first oxidation barrier layer is formed.

[0026] The reason for adopting the above-mentioned distributed differentiated ultraviolet laser oxidation process is that: the present invention finds that the oxidation barrier layer formed by the conventional one-step ultraviolet laser oxidation process is often not dense enough, which easily increases the risk of boron atoms and phosphorus atoms expanding into the bottom i-poly-Si layer during the subsequent boron diffusion and phosphorus diffusion, thereby causing battery leakage or performance degradation. The above-mentioned distributed differentiated ultraviolet laser oxidation process of the present invention can make the texture of the oxidation barrier layer denser. The principle is that different laser wavelengths penetrate into the silicon at different depths. In the first step, the wavelength is larger and the penetration depth is deeper, which can make the oxidation barrier layer on the surface of the i-poly-Si layer thicker; the second step has a shorter wavelength and a shallower penetration depth, which can make the oxidation barrier layer denser with almost unchanged thickness; at the same time, under different oxygen concentration treatment environments, the oxidation barrier layer can be formed to more effectively block the subsequent inward expansion of boron and phosphorus atoms, thereby improving battery performance.

[0027] Preferably, in S6, the process of forming the second oxidation barrier layer comprises: ultraviolet laser secondary patterning oxidation + -poly-Si layer, forming a second oxidation barrier layer; the wavelength of the ultraviolet laser is 300-400 nm, the power is 10-500 W, and the processing time is 1-20 s; generating a first oxidation barrier layer with a thickness of 20-300 nm.

[0028] As another preferred embodiment, in S6, the second oxidation barrier layer is formed by firstly performing ultraviolet laser oxidation treatment in a low-concentration oxygen environment and then performing ultraviolet laser oxidation treatment in a high-concentration oxygen environment, and finally forming a dense second oxidation barrier layer, which specifically includes:

[0029] First, under the conditions of an O2 flow rate of 10-100 sccm, an ambient oxygen concentration of 20-30%, an ultraviolet laser wavelength of 300-400 nm, a power of 10-500 W, and a treatment time of 1-20 s, the + - A second oxidation barrier layer with a thickness of 20 to 300 nm is formed on the surface of the poly-Si layer;

[0030] Then, under the conditions of an O2 flow rate of 100-500 sccm, an oxygen concentration of 30-80% in the environment, an ultraviolet laser wavelength of 200-300 nm, a power of 2-50 W, and a processing time of 1-20 s, a denser second oxide barrier layer is formed.

[0031] Preferably, in S1, the double-sided polishing process comprises: placing a single crystal silicon wafer with a resistivity of 1-12 Ω·cm, a minority carrier lifetime>2.5 ms, and a thickness of 100-200 μm into an alkaline polishing tank containing alkaline solution, and double-sided polishing for 6-8 min at 75-85°C, with a polishing thickness of 3-7 μm and a thinning amount of 0.35-0.45 g.

[0032] Preferably, in S2, tunneling SiO is deposited x When the O2 layer is formed, the gas flow rate is 10000~80000 sccm, the reaction temperature is 400~800℃, the time is 200~1000 s, and the tunneling SiO x The layer thickness is 2~10 nm.

[0033] Preferably, in S2, in the tunneling SiO x When the i-poly-Si layer is deposited on the Si layer, the gas flow rate of SiH4 is 300~2000 sccm, the reaction temperature is 500~700℃, the time is 2~4 h, the working gas pressure is 100~500 mTorr, and the thickness of the i-poly-Si layer is 100~300 nm.

[0034] Preferably, in S4, the boron diffusion process includes:

[0035] First, introduce a mixed gas of BCl3 and O2 at a temperature of 800-950°C, a diffusion time of 5-50 min, a BCl3 gas flow rate of 50-500 sccm, and an O2 flow rate of 500-2000 sccm;

[0036] O2 is then introduced for oxidation advancement, with a temperature of 900~1050℃, an advancement time of 30~80 min, and an O2 flow rate of 5000~30000 sccm to generate a BSG layer with a thickness of 30~70 nm.

[0037] Preferably, in S7, the phosphorus diffusion process includes:

[0038] First, introduce a mixed gas of POCl3 and O2 at a temperature of 750-850°C, a diffusion time of 5-30 min, a POCl3 flow rate carried by nitrogen of 500-1200 sccm, and an oxygen flow rate of 500-1000 sccm;

[0039] O2 is then introduced for oxidation advancement at a temperature of 850~950°C, an advancement time of 20~60 min, and an O2 flow rate of 1000~10000 sccm to generate a PSG layer with a thickness of 30~70 nm.

[0040] Preferably, in S8, the step of removing the coating on the front and side of the silicon wafer includes: using a chain etcher to remove the coating on the front and side of the silicon wafer, the volume ratio of the hydrofluoric acid solution and the nitric acid solution in the acid tank is 1:2~1:8, wherein the concentration of the hydrofluoric acid solution is 45~55 wt%, the concentration of the nitric acid solution is 65~75 wt%, and the belt speed is 1-10 m / min.

[0041] Preferably, in S9, the conditions for the laser grooving are: laser wavelength of 400-600 nm, frequency of 500-700 KHz, marking speed of 40000-50000 mm / s, power of 10-50 W, and processing time of 1-5 s.

[0042] Preferably, in S11, after the double-sided coating, a passivation anti-reflection layer is formed on the front and back surfaces, including AlO with a thickness of 8-10 nm. x thin films, and deposited on the AlO x SiN on thin film with a thickness of 80~120nm x film.

[0043] Compared with the prior art, the beneficial effects of the present invention are:

[0044] (1) The present invention adopts a single-layer i-poly-Si layer combined with ultraviolet laser patterned oxidation to form an oxidation barrier layer for doping diffusion to obtain a TBC solar cell. The entire preparation process only requires one i-poly-Si deposition and one laser grooving process, which can avoid the problems of uneven thermal stress distribution caused by multiple i-poly-Si depositions, resulting in reduced product performance and yield rate. At the same time, one laser grooving can reduce damage to the silicon wafer and improve V oc In addition, the use of a single polysilicon layer deposition can significantly reduce the use of special gases and reduce production costs.

[0045] (2) Compared with conventional processes such as deposition processes to prepare masks, the ultraviolet laser oxidation method used in the present invention can greatly shorten the preparation time of the mask (oxidation barrier layer) and improve the mask preparation efficiency and preparation accuracy. It is a simple, efficient and low-cost method and is expected to be used on a large scale in production lines.

[0046] (3) In the TBC solar cell prepared by the method of the present invention, the n + -ploy-Si layer and p + The height of the -ploy-Si layer is basically consistent, which is helpful for the preparation of subsequent electrode layers and can further improve the product yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1It is a structural schematic diagram of the TBC solar cell of the present invention.

[0048] Figure 2 It is a schematic diagram of the structure of the silicon wafer after cutting in Example 1 of the present invention.

[0049] Figure 3 It is a schematic diagram of the structure of a silicon wafer after double-sided polishing in Example 1 of the present invention.

[0050] Figure 4 The tunneling SiO deposited in Example 1 of the present invention x Schematic diagram of the silicon wafer structure after the layer and i-poly-Si layer.

[0051] Figure 5 It is a schematic diagram of the silicon wafer structure after the first oxidation barrier layer is generated in Example 1 of the present invention.

[0052] Figure 6 It is a schematic diagram of the structure of the silicon wafer after boron diffusion in Example 1 of the present invention.

[0053] Figure 7 It is a schematic diagram of the silicon wafer structure after the second oxidation barrier layer is generated in Example 1 of the present invention.

[0054] Figure 8 It is a schematic diagram of the silicon wafer structure after phosphorus diffusion in Example 1 of the present invention.

[0055] Fig. 9 It is a schematic diagram of the structure of the silicon wafer after laser grooving in Example 1 of the present invention.

[0056] Fig.10 It is a schematic diagram of the structure of the silicon wafer after the silicon wafer is textured in an embodiment of the present invention.

[0057] The reference numerals are: cutting line mark 1; N-type single crystal silicon wafer 2; tunneling SiO x Layer 3; i-poly-Si layer 4; first oxidation barrier layer 5; p + -ploy-Si layer 6; second oxidation barrier layer 7; n + -ploy-Si layer 8; pyramid velvet surface 9; front passivation anti-reflection layer 10; back passivation anti-reflection layer 11; electrode layer 12. DETAILED DESCRIPTION

[0058] The present invention will be further described below in conjunction with the embodiments.

[0059] A method for preparing a TBC solar cell comprises the following steps:

[0060] S1. Double-sided polishing of silicon wafers.

[0061] In some specific implementation cases, the double-sided polishing process includes: placing a single crystal silicon wafer with a thickness of 100~200 μm into an alkaline polishing tank containing alkaline solution, double-sided polishing for 6~8 min at 75~85°C, the polishing thickness is 3~7 μm, and the thinning amount is 0.35~0.45 g.

[0062] S2, deposit tunneling SiO on the back of the silicon wafer x layer, i-poly-Si layer.

[0063] Low-pressure chemical vapor deposition (LPCVD) has better step coverage capability, good composition and structure control, high deposition rate and output, and can greatly reduce particle pollution sources.

[0064] In some specific implementation cases, the tunneling SiO x When the O2 layer is formed, the gas flow rate is 10000~80000sccm, the reaction temperature is 400~800℃, the time is 200~1000 s, and the tunneling SiO x The layer thickness is 2~10 nm.

[0065] In some specific implementation cases, in the tunneling SiO x When the i-poly-Si layer is deposited on the Si layer, the gas flow rate of SiH4 is 300~2000 sccm, the reaction temperature is 500~700℃, the time is 2~4 h, the working gas pressure is 100~500 mTorr, and the thickness of the i-poly-Si layer is 100~300 nm.

[0066] S3, using ultraviolet laser to pattern and oxidize the surface of the i-poly-Si layer once, forming a first oxidation barrier layer. The patterned first oxidation barrier layer and the subsequent second oxidation barrier layer are interdigitated and complementary, and the two together just cover the entire i-poly-Si layer. The first oxidation barrier layer corresponds to the n in the subsequent process. + -ploy-Si (phosphorus-doped polysilicon) layer, the unblocked area is diffused by boron atoms during the boron diffusion process to form p + -ploy-Si (boron-doped polysilicon) layer; the second oxide barrier layer corresponds to the subsequent process p + -ploy-Si layer, the unblocked area is diffused by phosphorus atoms to form n + -ploy-Si layer.

[0067] In some specific implementation cases, the process of forming the first oxidation barrier layer includes: once patterning and oxidizing the i-poly-Si layer with an ultraviolet laser, +-poly-Si region forms a first oxidation barrier layer; the wavelength of the ultraviolet laser is 300-400 nm, the power is 10-500 W, and the processing time is 1-20 s; a first oxidation barrier layer with a thickness of 20-300 nm is generated.

[0068] In the above process, oxygen or ozone is dissociated into oxygen ions under the action of the laser emitted by the ultraviolet laser, and the oxygen ions react with the surface of the silicon wafer to form a silicon oxide layer (oxidation barrier layer) as a mask. In this process, the laser emitted by the laser heats the silicon wafer at the same time, which is conducive to promoting the rapid oxidation reaction of the oxygen ions and the silicon wafer to form a silicon oxide layer as a mask. The mask preparation can be completed quickly. Compared with the method of preparing the mask by deposition process, the mask preparation time can be greatly shortened, and the mask preparation efficiency and preparation accuracy can be improved.

[0069] In some more preferred implementation cases, the first oxidation barrier layer is formed by firstly performing an ultraviolet laser oxidation treatment in a low-concentration oxygen environment and then performing an ultraviolet laser oxidation treatment in a high-concentration oxygen environment, and finally forming a dense first oxidation barrier layer. Specifically, the process includes:

[0070] First, under the conditions of 10-100 sccm O2 flow rate, 20-30% oxygen concentration in the environment, 300-400 nm UV laser wavelength, 10-500 W power, and 1-20 s treatment time, the pre-set n + -A first oxidation barrier layer with a thickness of 20 to 300 nm is generated on the surface of the poly-Si layer area.

[0071] Then, under the conditions of an O2 flow rate of 100-500 sccm, an oxygen concentration of 30-80% in the environment, an ultraviolet laser wavelength of 200-300 nm, a power of 2-50 W, and a processing time of 1-20 s, a denser first oxidation barrier layer is formed.

[0072] The reason for adopting the above-mentioned distributed differentiated ultraviolet laser oxidation process is that: the present invention finds that the oxidation barrier layer formed by the conventional one-step ultraviolet laser oxidation process is often not dense enough, which easily increases the risk of boron atoms and phosphorus atoms expanding into the bottom i-poly-Si layer during the subsequent boron diffusion and phosphorus diffusion, thereby causing the battery performance to decline or leakage. The above-mentioned distributed differentiated ultraviolet laser oxidation process of the present invention can make the texture of the added oxidation barrier layer denser. The principle is that different laser wavelengths penetrate into the silicon at different depths. In the first step, the wavelength is larger and the penetration depth is deeper, which can make the oxidation barrier layer on the surface of the i-poly-Si layer thicker; the second step has a shorter wavelength and a shallower penetration depth, which can make the oxidation barrier layer denser with almost unchanged thickness; at the same time, under different oxygen concentration treatment environments, the oxidation barrier layer can be formed to more effectively block the subsequent inward expansion of boron and phosphorus atoms.

[0073] S4, the i-poly-Si layer containing the first oxidation barrier layer is subjected to boron diffusion. Boron atoms in the region with the first oxidation barrier layer are difficult to enter the bottom i-poly-Si layer, so that the intrinsic polysilicon characteristics can still be maintained; the i-poly-Si layer in the region without the oxidation barrier layer can be transformed into p-type silicon during the boron diffusion process. + -poly-Si layer, and at the same time generate a BSG layer (borosilicate glass layer) on the surface.

[0074] In some specific implementation cases, the boron diffusion process includes:

[0075] First, introduce a mixed gas of BCl3 and O2 at a temperature of 800-950°C, a diffusion time of 5-50 min, a BCl3 gas flow rate of 50-500 sccm, and an O2 flow rate of 500-2000 sccm;

[0076] O2 is then introduced for oxidation advancement, with a temperature of 900~1050℃, an advancement time of 30~80 min, and an O2 flow rate of 5000~30000 sccm to generate a BSG layer with a thickness of 30~70 nm.

[0077] S5, removing the first oxidation barrier layer and the BSG layer. The first oxidation barrier layer and the BSG layer covering the surface of the i-poly-Si layer are removed. + -The BSG layer on the surface of the p-ploy-Si layer is for the subsequent + The surface of the -poly-Si layer is oxidized by ultraviolet laser to form a second oxidation barrier layer, and the remaining i-poly-Si layer is exposed to the outside for phosphorus diffusion, which facilitates the entry of phosphorus atoms. After removing the first oxidation barrier layer and BSG layer, the back of the silicon wafer is a cross-spaced i-poly-Si layer and p-poly-Si layer. + -ploy-Si layer.

[0078] S6, using UV laser secondary patterning p + -poly-Si layer surface, forming a second oxidation barrier layer.

[0079] In some specific implementation cases, the second oxidation barrier layer is formed by: UV laser secondary patterning oxidation + -poly-Si layer, forming a second oxidation barrier layer; the wavelength of the ultraviolet laser is 300-400 nm, the power is 10-500 W, and the processing time is 1-20 s; a first oxidation barrier layer with a thickness of 20-300 nm is generated.

[0080] In some more preferred implementation cases, the second oxidation barrier layer is formed by firstly performing an ultraviolet laser oxidation treatment in a low-concentration oxygen environment and then performing an ultraviolet laser oxidation treatment in a high-concentration oxygen environment, and finally forming a dense second oxidation barrier layer, which specifically includes:

[0081] First, under the conditions of an O2 flow rate of 10-100 sccm, an ambient oxygen concentration of 20-30%, an ultraviolet laser wavelength of 300-400 nm, a power of 10-500 W, and a treatment time of 1-20 s, the + - A second oxidation barrier layer with a thickness of 20 to 300 nm is formed on the surface of the poly-Si layer;

[0082] Then, under the conditions of an O2 flow rate of 100-500 sccm, an oxygen concentration of 30-80% in the environment, an ultraviolet laser wavelength of 200-300 nm, a power of 2-50 W, and a processing time of 1-20 s, a denser second oxidation barrier layer is formed.

[0083] S7, diffuse phosphorus into the area without the second oxidation barrier layer to generate n + -poly-Si layer and PSG layer (phosphosilicate glass layer).

[0084] In some specific implementation cases, the phosphorus diffusion process includes:

[0085] First, introduce a mixed gas of POCl3 and O2 at a temperature of 750-850°C, a diffusion time of 5-30 min, a POCl3 flow rate carried by nitrogen of 500-1200 sccm, and an oxygen flow rate of 500-1000 sccm;

[0086] O2 is then introduced for oxidation advancement at a temperature of 850~950°C, an advancement time of 20~60 min, and an O2 flow rate of 1000~10000 sccm to generate a PSG layer with a thickness of 30~70 nm.

[0087] S8, remove the wrapping coating on the front and side of the silicon wafer. The present invention specifically removes the wrapping coating before laser grooving because the wrapping coating is generally removed by etching with an acid mixture to remove excess P + -ploy-Si layer and n + -poly-Si layer, if the groove is opened first and then the plating layer is removed, the i-poly-Si layer or the tunneling SiO x The layer or the silicon wafer itself is corroded by the acid, thus affecting the performance of the battery after preparation.

[0088] In some specific implementation cases, the step of removing the coating on the front and side of the silicon wafer includes: using a chain etcher to remove the coating on the front and side of the silicon wafer, the volume ratio of the hydrofluoric acid solution and the nitric acid solution in the acid tank is 1:2~1:8, wherein the concentration of the hydrofluoric acid solution is 45~55 wt%, the concentration of the nitric acid solution is 65~75 wt%, and the belt speed is 1-10 m / min.

[0089] S9, in p + -poly-Si layer and n + -Laser grooving at the junction of poly-Si layers.

[0090] In some specific implementation cases, the conditions for the laser grooving are: laser wavelength of 400-600 nm, frequency of 500-700 KHz, marking speed of 40000-50000 mm / s, power of 10-50 W, and processing time of 1-5 s.

[0091] S10, double-sided texturing and cleaning to remove the second oxidation barrier layer and the PSG layer.

[0092] After the texturing is completed, the remaining PSG layer and the second oxidation barrier layer on the back of the silicon wafer are further removed. Finally, a cross-spaced p-type structure is formed on the back of the silicon wafer. + -ploy-Si layer and n + -ploy-Si layer.

[0093] S11, double-sided coating, to form a passivation anti-reflection layer on the front and back sides. The passivation anti-reflection layer is plated on the surface of the preliminarily prepared silicon wafer. Its purpose is to: (1) reduce surface carrier recombination and improve V oc ; (2) Reduce light reflection and increase light absorption, thereby increasing photocurrent.

[0094] In some specific implementation cases, after the double-sided coating, a passivation anti-reflection layer is formed on the front and back surfaces, including AlO with a thickness of 8-10 nm. x thin films, and deposited on the AlO xSiN on thin film with a thickness of 80~120nm x film.

[0095] S12, screen printing, sintering, and light injection to obtain a TBC solar cell.

[0096] Specific examples and comparative examples.

[0097] Example 1

[0098] This embodiment is prepared based on an N-type single crystal silicon wafer. Specifically, the preparation method of the TBC solar cell in this embodiment includes the following steps:

[0099] Step S1, pre-processing of silicon wafers, including cutting and double-sided polishing: select N-type single crystal silicon wafers 2 cut by diamond wire, such as Figure 2 The figure shows an N-type single crystal silicon wafer 2 after cutting, one side of which has a cutting line mark 1 after cutting. The thickness of the silicon wafer after cutting is 150 μm and the size is 182.2 mm×186.7 mm. The silicon wafer is placed in an alkaline polishing tank containing alkaline solution and double-sided polishing is performed for 6 minutes at a temperature maintained at 75°C. Figure 3 As shown, the overall polishing thickness removed after polishing is 4 μm, and the thinning amount is 0.42 g.

[0100] Step S2: Depositing tunneling SiO on the back of the polished silicon wafer x Layer and i-poly-Si layer: Figure 4 Shown is the deposited tunneling SiO x Schematic diagram of the i-poly-Si layer and the i-poly-Si layer. On the back of the polished silicon wafer, low-pressure chemical vapor deposition (LPCVD) is used to grow tunneling SiO x Layer 3, O2 gas flow rate is 40000 sccm, temperature is 600℃, time is 600 s, the tunneling SiO grown x The thickness of layer 3 is about 3 nm. x After the growth of layer 3, the tunneling SiO x An i-poly-Si layer 4 is grown on the basis of layer 3, wherein the gas flow rate of SiH4 is 920 sccm, the temperature is 550°C, the time is 3.3 h, the working pressure is 300 mTorr, and the thickness of the grown i-poly-Si layer 4 is about 290 nm.

[0101] Step S3: UV laser once patterned oxidation of the i-poly-Si layer surface to form a first oxidation barrier layer: + -poly-Si layer area and n +-poly-Si layer area, an ultraviolet laser is used to cut the surface of the i-poly-Si layer (n + -poly-Si layer area) is patterned oxidized to form a dense first oxidation barrier layer on the patterned oxidized surface to block the entry of boron atoms into the area covered by the oxidation barrier layer during the subsequent boron diffusion process; the wavelength of the ultraviolet laser used is 355 nm, the power is 11 W, the O2 flow rate through the tube is 50 sccm, the oxygen concentration in the environment is 25% (volume ratio), and the oxidation treatment time is 10 s. A patterned first oxidation barrier layer of about 50 nm thick can be formed on the surface of the i-poly-Si layer 5, as shown in FIG. Figure 5 shown.

[0102] Step S4, performing boron diffusion in the area not protected by the first oxidation barrier layer: Figure 6 The figure shows the schematic diagram after boron diffusion. The high temperature boron diffusion method is used to form p + -poly-Si layer 6, a mixed gas of BCl3 and O2 was introduced during boron diffusion, the temperature was 850℃, the diffusion time was 10 min, the gas flow rate of BCl3 was 200 sccm, and the gas flow rate of O2 was 1200 sccm. After the initial diffusion was completed, O2 was introduced for oxidation promotion; the oxidation promotion temperature was 950℃, the gas flow rate of O2 was 7000 sccm, and the promotion time was 30 min. The thickness of the formed BSG was about 45 nm. Due to the existence of the first oxidation barrier layer, p-type BSG can be formed in the non-oxidized area of ​​the i-poly-Si layer. + -poly-Si layer 6.

[0103] Step S5, removing the first oxidation barrier layer and BSG layer: using a chain etcher to remove the BSG layer and the first oxidation barrier layer formed on the surface of the silicon wafer after boron diffusion, wherein the concentration of the hydrofluoric acid solution in the chain etcher is 40 wt%, and the belt speed is 3 m / min. After removing the first oxidation barrier layer and BSG layer, the back side of the silicon wafer is i-poly-Si layer and p-poly-Si layer interlaced and spaced from each other. + -poly-Si layer.

[0104] Step S6: UV laser secondary patterning oxidation + - Formation of a second oxidation barrier layer on the surface of the poly-Si layer: UV laser is used to +The surface of the -poly-Si layer is oxidized to form a dense second oxidation barrier layer on its surface to block the entry of phosphorus atoms in the subsequent phosphorus diffusion process; the area where the second oxidation barrier layer 7 is not formed is the area corresponding to the original first oxidation barrier layer, that is, the i-poly-Si layer that has not been diffused by boron atoms in the previous step; the wavelength of the ultraviolet laser used is 355 nm, the power is 11 W, the O2 flow rate through the tube is 50 sccm, the oxygen concentration in the environment is 25% (volume ratio), the oxidation treatment time is 10 s, and it can be obtained in p + -A second oxidation barrier layer 7 of about 50 nm is formed on the surface of the poly-Si layer, such as Figure 7 shown.

[0105] Step S7, diffusing phosphorus in the unprotected area of ​​the second oxidation barrier layer: Figure 8 The figure shows the schematic diagram after phosphorus diffusion. + -poly-Si layer area forms n + -poly-Si layer 8, a mixed gas of POCl3 and O2 is introduced during phosphorus diffusion, the diffusion temperature is 790℃, the diffusion time is 20 min, POCl3 is carried by nitrogen with a flow rate of 1100 sccm, and the gas flow rate of O2 is 700 sccm. After the initial diffusion is completed, O2 is introduced for oxidation promotion, the oxidation promotion temperature is 890℃, the gas flow rate of O2 is 3000 sccm, and the promotion time is 40 min; the thickness of PSG is about 42nm. Due to the existence of the second oxidation barrier layer, n-type ions can be formed in the non-oxidized area of ​​the i-poly-Si layer. + -poly-Si layer 8.

[0106] Step S8, removing the coating on the front and side of the silicon wafer: The silicon wafer after high temperature treatment is passed through a chain etching machine to remove the coating on the front and side of the silicon wafer, that is, other generated layers not belonging to the back of the silicon wafer. + -poly-Si layer / p + -poly-Si layer area, wherein the volume ratio of the hydrofluoric acid solution to the nitric acid solution in the acid tank is 1:4 (the concentration of the hydrofluoric acid solution is 49 wt%, and the concentration of the nitric acid solution is 69 wt%), and the belt speed is 1.3 m / min.

[0107] Step S9: + -poly-Si layer and p + - Laser grooving at the junction of poly-Si layers: Fig. 9 The figure shows the schematic diagram of laser grooving. + -poly-Si layer and p +-The junction of the poly-Si layer is laser grooved to create a band gap between the two regions for insulation isolation. The laser wavelength is 532 nm, the frequency is 600 KHz, the marking speed is 45000 mm / s, the power is 50 W, and the processing time is 3 s.

[0108] Step S10, double-sided texturing and removal of the second oxidation barrier layer and the PSG layer: Fig.10 The figure shows a schematic diagram of the texturing process. The laser grooved silicon wafer is placed in the texturing tank for texturing. The concentration of the KOH solution in the texturing tank is 1.7wt%, the temperature is maintained at 82℃, and the texturing time is 7 minutes. The thinning amount after texturing is 0.36 g. Since the front side of the silicon wafer has been completely removed from the coating and there is no oxidation area, an effective light-trapping velvet surface can be formed during the texturing process, such as Fig.10 The pyramid velvet surface 9 is located on the front side of the silicon wafer. The subsequent acid (HF / HCl) cleaning tank of the velvet tank can further remove the residual PSG layer and the second oxidation barrier layer of the silicon wafer.

[0109] Step S11, double-sided coating is performed on the front and back sides of the silicon wafer to form a passivation anti-reflection layer: Atomic layer deposition (ALD) is used to deposit AlO on the front and back sides of the processed silicon wafer. x The film is generated by the reaction of Al(CH3)3 and water vapor, with a thickness of 8nm and a process temperature of 250°C. Then SiN is deposited on both sides of the silicon wafer using a tubular PECVD device. x Thin film, SiN x The film thickness is about 90 nm and the refractive index is 2.0. x During thin film deposition, the reaction gases in the tubular chamber are SiH4 and NH3, the working pressure is 1600 mTorr, the power is 12000 W, the temperature is 440℃, the flow rate of SiH4 gas is 980 sccm, the flow rate of NH3 gas is 8000 sccm, the silicon-nitrogen ratio is 1:5, and the deposition time is 10 min.

[0110] Step S12, generate an electrode layer through screen printing + sintering + light injection to obtain a finished battery: the coated silicon wafer is screen-printed on the back to form a metal contact, and then sintered at 770°C to form an Ag-Si ohmic contact to form an electrode layer, and finally repaired by light injection to obtain the final finished battery.

[0111] like Figure 1 The figure shows the structure of the TBC solar cell after the preparation. The front side of the silicon wafer is provided with a pyramid velvet surface 9, and the back side of the silicon wafer is provided with n velvet surfaces 9 arranged alternately at intervals. + -poly-Si layer 8 and p + -poly-Si layer 6; n + -poly-Si layer 8 and p+ - There is a tunneling SiO between the poly-Si layer 6 and the silicon wafer. x Layer 3; adjacent n + -poly-Si layer 8 and p + -There are gaps between the poly-Si layers 9, and pyramid velvet surfaces 9 are also present in the gaps. + -poly-Si layer 8 or p + -poly-Si layer 6 is usually provided with Ag electrodes in electrode layer 12. A front passivation anti-reflection layer 10 is plated on the pyramid velvet surface 9 on the front side of the silicon wafer, and a back passivation anti-reflection layer 11 is also plated on the back side of the silicon wafer. + -poly-Si layer 8 and p + - The height of the poly-Si layer 6 is substantially the same without obvious height difference, which is conducive to the subsequent preparation of the electrode layer through screen printing and sintering, thereby improving the yield rate of the product.

[0112] In the present invention, a single-layer i-poly-Si layer is combined with ultraviolet laser oxidation to form a mask for doping diffusion to obtain a TBC solar cell. The entire preparation process only requires one i-poly-Si layer deposition and one laser grooving process. Compared with the existing multiple deposition and grooving technology, the uneven distribution of thermal stress caused by multiple polysilicon layer depositions leads to reduced yield and other problems, and the damage to the silicon substrate caused by laser grooving can be reduced. Compared with multiple depositions, the use of a single polysilicon layer deposition can greatly reduce the amount of special gas and reduce the preparation cost. In addition, compared with the existing technology that also uses a single-layer i-poly-Si layer but prepares batteries by printing phosphorus slurry and boron slurry for drying and annealing, it can not only avoid the reduction of battery performance caused by the residue of phosphorus slurry and boron slurry on the silicon wafer (phosphorus slurry and boron slurry are difficult to clean and usually produce residues), but also avoid the pollution of the environment by the slurry in the production process (the process used in the present invention can realize gas recovery, prevent air pollution, and the recovered gas can be processed and reused).

[0113] Example 2

[0114] The difference between Example 2 and Example 1 is that in S3 and S6, a distributed differentiated purple laser oxidation process is adopted:

[0115] S3: First, under the conditions of an O2 flow rate of 50 sccm, an oxygen concentration of 25% (volume ratio) in the environment, a UV laser wavelength of 355 nm, a power of 11 W, and a processing time of 10 s, the pre-set n +-poly-Si layer area surface generated about 50 nm thick first oxidation barrier layer. Then under the conditions of O2 flow rate of 200 sccm, oxygen concentration of 50% (volume ratio) in the environment, UV laser wavelength of 266 nm, power of 3 W, and treatment time of 17 s, a more dense first oxidation barrier layer was formed.

[0116] S6: First, under the conditions of an O2 flow rate of 50 sccm, an oxygen concentration of 25% (volume ratio) in the environment, a UV laser wavelength of 355 nm, a power of 11 W, and a treatment time of 10 s, at p + -poly-Si layer surface to form a second oxidation barrier layer with a thickness of about 50 nm. Then, under the conditions of 200 sccm of O2 flow rate, 50% (volume ratio) of oxygen concentration in the environment, 266 nm of ultraviolet laser wavelength, 3 W of power, and 17 s of treatment time, a more dense second oxidation barrier layer is formed.

[0117] Example 3

[0118] Step S1, select an N-type single crystal silicon wafer cut by diamond wire, with a thickness of 150 μm and a size of 182.2 mm×186.7 mm. Put the silicon wafer into an alkaline polishing tank, maintain the temperature at 75°C, perform double-sided polishing for 6 min, the polishing thickness is 4 μm, and the thinning amount is 0.42 g.

[0119] Step S2: growing tunneling SiO on the polished silicon wafer surface by LPCVD x layer, the gas flow rate of O2 is 40000 sccm, the temperature is 600℃, the time is 600 s, and the tunneling SiO x The layer thickness is 3 nm; then tunneling SiO x An i-poly-Si layer is grown again on the layer, with a SiH4 gas flow rate of 920 sccm, a temperature of 550°C, a time of 3.3 h, a working gas pressure of 300 mTorr, and a thickness of the i-poly-Si layer of about 290 nm.

[0120] Step S3, using an ultraviolet laser to perform patterned oxidation on the surface of the i-poly-Si layer, so that a dense first oxide barrier layer is formed on the patterned surface, which is a prerequisite for blocking the entry of boron atoms in the subsequent boron diffusion process; the ultraviolet laser wavelength used is 355 nm, the power is 11 W, the O2 flow rate through the tube is 50 sccm, the oxygen concentration in the environment is 25% (volume ratio), the processing time is 10 s, and a first oxide barrier layer with a thickness of about 50 nm can be formed on the surface of the patterned i-poly-Si layer.

[0121] Step S4: using a high temperature boron diffusion method to form p+ -poly-Si layer, boron diffusion temperature 850℃, diffusion time 10 min, BCl3 gas flow rate 200 sccm, O2 gas flow rate 1200 sccm, oxidation push temperature 950℃, O2 flow rate 7000 sccm, push time 30 min, BSG layer thickness is about 45 nm, due to the existence of the first oxidation barrier layer, p can be formed in the non-oxidation layer position + -poly-Si layer.

[0122] Step S5: Use green picosecond laser to pattern and groove the first oxide barrier layer to loosen the first oxide barrier layer. The laser wavelength used is 532 nm, the frequency is 600 KHz, the marking speed is 45000 mm / s, the power is 50 W, and the processing time is 3 s.

[0123] Step S6: After that, the laser grooved position is cleaned with wet alkali to remove the first oxidation barrier layer on the surface and expose the bottom i-poly-Si layer. The temperature is 75°C and the time is 180 s. Since there is a BSG layer in the non-oxidized area, the BSG layer can protect the bottom p-type silicon layer during the wet cleaning process. + -The poly-Si layer is not damaged.

[0124] Step S7: using a high temperature phosphorus diffusion method to + -poly-Si layer area forms n + -poly-Si layer, phosphorus diffusion temperature 790℃, diffusion time 20 min, POCl3 carried by nitrogen with a flow rate of 1100 sccm, O2 flow rate 700 sccm, oxidation push temperature 890℃, O2 flow rate 3000 sccm, push time 40 min, PSG layer thickness is about 42 nm, due to the existence of BSG layer can prevent phosphorus atoms from diffusing into the bottom p + -poly-Si layer, to prevent the layer from being inverted, while the non-BSG layer area can form n + -poly-Si layer.

[0125] Step S8: After high temperature treatment, the silicon wafer is passed through a chain etching machine to remove the n-plated + -poly-Si layer and p + -poly-Si layer area, wherein the volume ratio of the hydrofluoric acid solution to the nitric acid solution in the acid tank is 1:4 (the concentration of the hydrofluoric acid solution is 49 wt%, and the concentration of the nitric acid solution is 69 wt%), and the belt speed is 1.3 m / min.

[0126] Step S9: Then, use picosecond laser to + -poly-Si layer and p +-poly-Si layer junction is laser grooved to make n + -poly-Si layer and p + -poly-Si layer for insulation isolation, laser wavelength is 532 nm, frequency is 600 KHZ, marking speed is 45000 mm / s, power is 50 W, and processing time is 3 s.

[0127] Step S10, put the laser grooved silicon wafer into the texturing tank for texturing, wherein the concentration of KOH solution in the texturing tank is 1.7 wt%, the temperature is maintained at 82°C, the texturing time is 7 min, and the thinning amount is 0.36 g. Since the coating layer on the front of the silicon wafer has been completely removed and there is no oxidation area, an effective light-trapping velvet surface can be formed during the texturing process, and there are PSG and BSG layers in the non-laser-processed area on the back, which can effectively protect the area from being damaged during the texturing process. The laser-processed poly-Si layer area can be further corroded during the texturing process, thereby forming an insulating Gap velvet area. The subsequent acid (HF / HCl) cleaning tank of the texturing tank body can further remove the residual PSG and BSG layers on the silicon wafer.

[0128] Step S11: Deposit AlO on the front and back sides of the processed silicon wafer by ALD deposition method. x The film is generated by the reaction of Al(CH3)3 and water vapor, with a thickness of 8 nm and a process temperature of 250°C. Then, SiN is deposited on both sides using a tubular PECVD device. x Film, front SiN x The thickness of the film is about 82 nm, and the refractive index is 2.1; the back SiN x The thickness of the film is about 90 nm and the refractive index is 2.0; the reaction gases in the tubular cavity are SiH4 and NH3, the working pressure is 1600 mTorr, the power is 12000 W, the temperature is 440℃, the SiH4 gas flow rate is 980 sccm, the NH3 gas flow rate is 8000 sccm, the silicon-nitrogen ratio is 1:5, and the deposition time is 10 min.

[0129] Step S12, screen-printing the coated sheet on the back to form metal contact, then sintering at 770° C. to form Ag-Si ohmic contact, and finally performing light injection repair to obtain the final finished TBC battery.

[0130] Comparative Example 1 (using the existing HPBC solar cell as a comparison)

[0131] S1. Select a P-type single crystal silicon wafer cut with diamond wire, with a thickness of 150 μm and a size of 182.2 mm×186.7 mm. Put the wafer into an alkali polishing tank containing alkali solution, maintain the temperature at 75°C, and perform double-sided polishing for 6 min. The polishing thickness is 4 μm and the thinning amount is 0.42 g.

[0132] S2, using LPCVD to grow tunneling SiO on the polished silicon wafer surface x layer, the O2 gas flow rate is 40000 sccm, the temperature is 600℃, the time is 600 s, and the tunneling SiO grown x The layer thickness is about 3 nm; then tunneling SiO x An i-poly-Si layer is grown again on the layer, with a SiH4 gas flow rate of 920 sccm, a temperature of 550 °C, a time of 1.5 h, a working gas pressure of 300 mTorr, and a thickness of the i-poly-Si layer of about 180 nm.

[0133] S3, use high temperature phosphorus diffusion method to transform the i-poly-Si layer into n + -poly-Si layer, phosphorus diffusion temperature 790℃, diffusion time 15 min, POCl3 is carried by nitrogen with a flow rate of 1000 sccm, O2 flow rate is 650 sccm, oxidation push temperature 890℃, O2 flow rate is 3000 sccm, push time is 20 min, PSG layer thickness is about 39 nm.

[0134] S4, using picosecond laser + -poly-Si layer is used for patterned laser grooving, with a laser wavelength of 532 nm, a frequency of 600 KHz, a marking speed of 45000 mm / s, a power of 25 W, and a processing time of 2.7 s.

[0135] S5, the processed silicon wafer is passed through a chain etching machine to remove the n-plated + -poly-Si layer, wherein the volume ratio of the hydrofluoric acid solution to the nitric acid solution in the acid tank is 1:4 (the concentration of the hydrofluoric acid solution is 49 wt%, and the concentration of the nitric acid solution is 69 wt%), and the belt speed is 1.6 m / min.

[0136] S6. Put the laser grooved silicon wafer into the alkaline texturing tank for cleaning and texturing, where the KOH solution concentration is 1.7wt%, the temperature is maintained at 80℃, the time is 7 min, and the thinning amount is 0.35 g; on the one hand, the laser grooved area on the back can be cleaned to expose the bottom p-type silicon substrate; on the other hand, an effective light-trapping texture surface can be formed on the front of the silicon wafer. Then the acid (HF / HCl) cleaning tank of the texturing tank body further removes the residual PSG layer of the silicon wafer.

[0137] S7, using ALD deposition method to deposit AlO on the front and back sides of the processed silicon wafer x The film is generated by the reaction of Al(CH3)3 and water vapor, with a thickness of 8 nm and a process temperature of 250°C. Then, SiN is deposited on both sides using a tubular PECVD device. x Film, front SiN x The thickness of the film is about 82 nm, and the refractive index is 2.1; the back SiN x The thickness of the film is about 90 nm and the refractive index is 2.0; the reaction gases in the tubular cavity are SiH4 and NH3, the working pressure is 1600 mTorr, the power is 12000 W, the temperature is 440℃, the SiH4 gas flow rate is 980 sccm, the NH3 gas flow rate is 8000 sccm, the silicon-nitrogen ratio is 1:5, and the deposition time is 10 min.

[0138] S8. The coated silicon wafer is screen-printed on the back to form a metal contact, and then sintered at 750°C to form an Ag-Si ohmic contact. Finally, the finished battery is obtained through light injection repair.

[0139] Comparative Example 2 (using two deposition poly-Si layers + two laser grooving processes)

[0140] S1. Select N-type single crystal silicon wafers cut with diamond wire, with a thickness of 150 μm and a size of 182.2 mm×186.7 mm. Put the cut silicon wafers into an alkaline polishing tank, maintain the temperature at 75°C, and perform double-sided polishing for 6 min. The polishing thickness is 4 μm and the thinning amount is 0.42 g.

[0141] S2, then the back surface of the polished silicon wafer is firstly grown by LPCVD tunneling SiO x layer, the gas flow rate of O2 is 40000 sccm, the temperature is 600℃, the time is 600 s, and the tunneling SiO x The layer thickness is about 3 nm; then tunneling SiO xAn i-poly-Si layer is grown again on the layer, with a SiH4 gas flow rate of 920 sccm, a temperature of 550 °C, a time of 3.3 h, a working gas pressure of 300 mTorr, and a thickness of the i-poly-Si layer of about 290 nm.

[0142] S3, then use high temperature boron diffusion method to transform the i-poly-Si layer into p + -poly-Si layer, boron diffusion temperature 850℃, diffusion time 10 min, BCl3 gas flow rate 200 sccm, O2 gas flow rate 1200 sccm, oxidation push temperature 950℃, O2 flow rate 7000 sccm, push time 30 min, BSG layer thickness is about 45 nm.

[0143] S4. Use picosecond laser to perform a patterned grooving of the BSG layer. The laser wavelength used is 532 nm, the frequency is 600 KHZ, the marking speed is 45000 mm / s, the power is 50 W, and the processing time is 3 s.

[0144] S5. The silicon wafer after laser patterning and slotting is placed in an alkaline solution for cleaning at a temperature of 75°C for 360 s and a corrosion depth of 1.7 μm.

[0145] S6, then use LPCVD to grow tunnel SiO x layer, the gas flow rate of O2 is 30000 sccm, the temperature is 600℃, the time is 450 s, and the tunneling SiO x The layer thickness is about 2.5 nm; then tunneling SiO x An i-poly-Si layer is grown again on the layer, with a SiH4 gas flow rate of 920 sccm, a temperature of 550 °C, a time of 1.5 h, a working gas pressure of 300 mTorr, and a thickness of the i-poly-Si layer of about 180 nm.

[0146] S7, using phosphorus diffusion method to form n + -poly-Si layer, phosphorus diffusion temperature 790℃, diffusion time 15 min, POCl3 is carried by nitrogen with a flow rate of 1000 sccm, O2 flow rate is 650 sccm, oxidation push temperature 890℃, O2 flow rate is 3000 sccm, push time is 20 min, PSG layer thickness is about 39 nm.

[0147] S8, then use picosecond laser to perform secondary patterning to open the PSG layer, so that p + -poly bottom corresponds to PSG layer and p +-poly and n + The PSG layer at the junction area of ​​-poly was loosened with a laser wavelength of 532 nm, a frequency of 600 KHz, a marking speed of 45000 mm / s, a power of 25 W, and a processing time of 2.7 s.

[0148] S9, using a chain machine to remove the n-plated silicon wafers on the front and side surfaces of the silicon wafers. + -poly-Si and p + -poly-Si layer, wherein the volume ratio of the hydrofluoric acid solution to the nitric acid solution in the acid tank is 1:4 (the concentration of the hydrofluoric acid solution is 49 wt %, and the concentration of the nitric acid solution is 69 wt %), and the belt speed is 1.3 m / min.

[0149] S10, put the silicon wafer that has been deplated into an alkaline texturing tank for wet cleaning of the laser slotted area on the back and integrated texturing of the front. The KOH solution concentration in the texturing tank is 1.7 wt%, the temperature is maintained at 82°C, the time is 7 min, and the weight is reduced by 0.36 g for cleaning and texturing. Since the silicon wafer has been deplated and there is no oxidation area on the front side, an effective light-trapping texture surface can be formed during the texturing process; and in the laser patterning area on the back side, the alkaline solution can effectively corrode the bottom poly-Si to form an isolated insulating structure. The subsequent acid (HF / HCl) cleaning tank of the texturing tank can further remove the residual PSG layer and BSG layer of the silicon wafer.

[0150] S11, using ALD deposition method to deposit AlO on the front and back sides of the processed silicon wafer x The film is generated by the reaction of Al(CH3)3 and water vapor, with a thickness of 8 nm and a process temperature of 250°C. Then, SiN is deposited on both sides using a tubular PECVD device. x Film, front SiN x The thickness of the film is about 82 nm, and the refractive index is 2.1; the back SiN x The thickness of the film is about 90 nm and the refractive index is 2.0; the reaction gases in the tubular cavity are SiH4 and NH3, the working pressure is 1600 mTorr, the power is 12000 W, the temperature is 440℃, the SiH4 gas flow rate is 980 sccm, the NH3 gas flow rate is 8000 sccm, the silicon-nitrogen ratio is 1:5, and the deposition time is 10 min.

[0151] S12. The coated sheet is screen-printed on the back to form a metal contact, and then sintered at 770°C to form an Ag-Si ohmic contact. Finally, the final TBC finished battery is obtained through light injection repair.

[0152] Performance Testing

[0153] The electrical performance of the solar cells prepared in each embodiment and each comparative example was tested, and the data are shown in the following table:

[0154]

[0155] From the data in the above table, we can see that:

[0156] The data of various performances of each embodiment are obviously better than those of each comparative example. Among them, the main difference between comparative example 2 and embodiment 1 is that the traditional process of depositing i-poly-Si twice and laser grooving twice is adopted. Multiple i-poly-Si depositions are prone to cause uneven distribution of thermal stress, resulting in reduced product performance; at the same time, multiple laser grooving will increase the damage to the silicon wafer, thereby reducing V oc In addition, the use of multiple i-poly-Si deposition will significantly increase the amount of special gases used and increase production costs.

[0157] In addition, compared with Example 1, Example 2 differs only in that a distributed differentiated UV laser oxidation process is used. The oxidation barrier layer formed by the conventional one-step UV laser oxidation process is often not dense enough, which easily increases the risk of boron atoms and phosphorus atoms expanding into the bottom i-poly-Si layer during the subsequent boron diffusion and phosphorus diffusion process, thereby causing battery performance degradation or leakage. The use of a distributed differentiated UV laser oxidation process can make the oxidation barrier layer denser without increasing the thickness, so it can more effectively block the subsequent expansion of boron and phosphorus atoms, thereby improving battery performance.

[0158] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0159] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a TBC solar cell, characterized in that include: S1, double-sided polishing of silicon wafer; S2, backside deposition tunneling SiO x layer, i-poly-Si layer; S3, using an ultraviolet laser to pattern and oxidize the i-poly-Si layer once to form a first oxidation barrier layer; S4, Boron diffusion, generating p in the unoxidized area + -poly-Si layer and BSG layer; S5, removing the first oxidation barrier layer and the BSG layer; S6, UV laser secondary patterning oxidation + -poly-Si layer, forming a second oxidation barrier layer; S7, phosphorus diffusion, generating n in the area without the second oxidation barrier layer + -poly-Si layer and PSG layer; S8, removing the coating; S9, in p + -poly-Si layer and n + - Laser grooving at the interface of poly-Si layer; S10, cleaning and velveting; S11, double-sided coating; S12, screen printing, sintering, and light injection to obtain a TBC solar cell; S3 and S6 include: first generating a 20-300 nm oxidation barrier layer at an oxygen concentration of 20-30%, an oxygen flow rate of 10-100 sccm, a laser wavelength of 300-400 nm, a power of 10-500 W, and a time of 1-20 s; and then forming a denser oxidation barrier layer at an oxygen concentration of 30-80%, an oxygen flow rate of 100-500 sccm, a laser wavelength of 200-300 nm, a power of 2-50 W, and a time of 1-20 s.

2. The preparation method according to claim 1, characterized in that: In S2, the tunneling SiO x The thickness of the layer is 2~10nm.

3. The preparation method according to claim 2, characterized in that: In S2, tunneling SiO is deposited x When the layer is formed, the O2 flow rate is 10000~80000 sccm, the reaction temperature is 400~800℃, and the time is 200~1000 s.

4. The preparation method according to claim 1 or 3, characterized in that: In S2, the thickness of the i-poly-Si layer is 100-300 nm.

5. The preparation method according to claim 4, characterized in that: In S2, the tunneling SiO x When the i-poly-Si layer is deposited on the SiO2 layer, the SiH4 gas flow rate is 300~2000 sccm, the reaction temperature is 500~700℃, the time is 2~4 h, and the working gas pressure is 100~500 mTorr.

6. The preparation method according to claim 1, characterized in that: In S4, the boron diffusion process includes: First, introduce a mixed gas of BCl3 and O2 at a temperature of 800-950°C, a diffusion time of 5-50 min, a BCl3 gas flow rate of 50-500 sccm, and an O2 flow rate of 500-2000 sccm; O2 is then introduced for oxidation advancement, with a temperature of 900~1050℃, an advancement time of 30~80 min, and an O2 flow rate of 5000~30000 sccm to generate a BSG layer with a thickness of 30~70 nm.

7. The preparation method according to claim 1, characterized in that: In S7, the phosphorus diffusion process includes: First, introduce a mixed gas of POCl3 and O2 at a temperature of 750-850°C, a diffusion time of 5-30 min, a POCl3 flow rate carried by nitrogen of 500-1200 sccm, and an oxygen flow rate of 500-1000 sccm; O2 is then introduced for oxidation advancement at a temperature of 850~950°C, an advancement time of 20~60 min, and an O2 flow rate of 1000~10000 sccm to generate a PSG layer with a thickness of 30~70 nm.

8. The preparation method according to claim 1, characterized in that: In S8, the step of removing the wrap-around coating on the front and side surfaces of the silicon wafer includes: using a chain etcher to remove the wrap-around coating on the front and side surfaces of the silicon wafer.

9. The preparation method according to claim 1, characterized in that: In S9, the conditions for the laser grooving are: laser wavelength of 400-600 nm, frequency of 500-700 KHz, marking speed of 40000-50000 mm / s, power of 10-50 W, and processing time of 1-5 s.

10. The preparation method according to claim 1, characterized in that: In S11, after the double-sided coating, a front passivation anti-reflection layer is generated on the front side and a back passivation anti-reflection layer is generated on the back side.

Citation Information

Cited By

  • TBC battery and preparation method thereof

    CN120769588A

  • A tbc cell and method of making the same

    CN120769588B